Early Mesozoic Southward Subduction of the Eastern Mongol–Okhotsk Oceanic Plate: Evidence from Zircon U–Pb–Hf Isotopes and Whole‐rock Geochemistry of Triassic Granitic Rocks in the Mohe Area, NE China. Issue 4 (22nd September 2016) - Li, Liang; Sun, Fengyue; Li, Bile; Xu, Qinglin; Zhang, Yajing; Qian, Ye
Abstract: In this paper, we present new U–Pb zircon ages, Hf isotope data and major and trace elements for Early Mesozoic granitic rocks in Mohe area in the Erguna Massif of northeast China to elucidate the southward subduction of the eastern Mongol–Okhotsk Oceanic plate in Early Mesozoic. Zircons from two representative intrusions, syenogranites and monzogranites, in the Mohe area are euhedral–subhedral in shape, display oscillatory growth zoning in cathodoluminescence (CL) images, and have Th/U ratios of 0.10–0.72, and in combination these features indicating that the zircons are of igneous origin. U–Pb zircon dating results demonstrate that the syenogranites formed at 245.1 ± 1.4 Ma and monzogranites formed at 212.2 ± 1.7 Ma. These granitic rocks are characterized by high SiO2, Al2 O3 and (Na2 O + K2 O), low TFeO, MgO, TiO2 and P2 O5 concentrations, belonging to the high‐K calc‐alkaline series. They are enriched in LREE and large ion lithophile elements (e.g., Rb, K, and Sr), depleted in HREE and high field strength elements (e.g., Nb, Ta, Th, and Ti), as well as very weak negative Eu anomalies (Eu/Eu* = 0.48 1.01). Their zircon εHf(t) values range from −7.9 to −2.0 and range from 0.20 to 0.49, in response to their two‐stage Hf model ages (TDM2 ) range from 1.40 Ga to 1.77 Ga range from 0.94 Ga to 1.24 Ga, respectively, indicating that primary magmas of syenogranites were derived from partial melting of newly accreted juvenile crustal material that formed from the enriched mantle during the Mesoproterozoic, monzogranites are generated by partial melting of newly accreted juvenile crustal material that formed from the depleted mantle during the Meso‐ to Neoproterozoic. We conclude, therefore, that the early Mesozoic granitic rocks of the Mohe area are associated with the continuous southward subduction of the Mongol–Okhotsk oceanic plate rather than the Paleo‐Asian and circum‐Pacific tectonic regimes. Abstract : The Early Mesozoic granitic rocks in the Erguna, NE China, have different sources of primary magma. And they are associated with the continuous southward subduction of the Mongol–Okhotsk oceanic plate rather than the Paleo‐Asian and circum‐Pacific tectonic regimes.